2022
DOI: 10.1016/j.ajogmf.2021.100523
|View full text |Cite
|
Sign up to set email alerts
|

Stillbirth and fetal capillary infection by SARS-CoV-2

Abstract: We present the case of a stillbirth in a paucisymptomatic mother affected by SARS-CoV-2. At gross examination, the placenta showed a diffuse marbled appearance and a focal hemorrhagic area. Multiple areas of hemorrhagic/ischemic necrosis with central and peripheral villous infarctions and thrombosis of several maternal and fetal vessels with luminal fibrin and platelet deposition was observed. All the lesions appeared to be synchronous. Virus particles were identified by Electron Microscopy within the cytoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 8 publications
(4 reference statements)
0
16
0
Order By: Relevance
“…In pregnant women, the specific clinical manifestation of SARS-CoV-2 infection remains unclear [19]. Only sporadic cases of vertical transmission were previously described [22]. Identifying molecular changes occurring in the maternal-fetal interface in pregnant women with COVID-19 represents a major challenge.…”
Section: Resultsmentioning
confidence: 99%
“…In pregnant women, the specific clinical manifestation of SARS-CoV-2 infection remains unclear [19]. Only sporadic cases of vertical transmission were previously described [22]. Identifying molecular changes occurring in the maternal-fetal interface in pregnant women with COVID-19 represents a major challenge.…”
Section: Resultsmentioning
confidence: 99%
“…Our data from these 68 cases support previous case reports suggesting that placental insufficiency is responsible for perinatal deaths occurring with SARS-CoV-2 placentitis. 58,[91][92][93][94][95][96][97] In summary, we found that SARS-CoV-2 placentitis can cause extensive placental damage as a result of destructive lesions, and that the damage can be further exacerbated by additional pathology abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive intervillous fibrin deposition, involving up to 70% or more of the placental tissues in one case, was present in the placentas from all 5 fetuses. Following this report, additional case reports of the placental pathology from stillborn fetuses delivered to mothers with COVID-19 were reported that showed all the placentas to be markedly abnormal and extensively involved with similar destructive features–increased or massive intervillous fibrin deposition, villous trophoblast necrosis, and chronic histiocytic intervillositis [ 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ]. In their report of a stillbirth from a mother having COVID-19 at 30 weeks 4 days gestation in Bratislava, Biringer et al [ 80 ] believed the cause of death to be acute placental insufficiency based upon their findings of placental destruction due to SARS-CoV-2 placentitis and an autopsy revealing fetal organs to have no morphological abnormalities.…”
Section: Covid-19 Infection and Stillbirthmentioning
confidence: 97%
“…In their report of a stillbirth from a mother having COVID-19 at 30 weeks 4 days gestation in Bratislava, Biringer et al [ 80 ] believed the cause of death to be acute placental insufficiency based upon their findings of placental destruction due to SARS-CoV-2 placentitis and an autopsy revealing fetal organs to have no morphological abnormalities. In another case of probable placental insufficiency causing stillbirth, di Gioia et al [ 79 ] described a mother with COVID-19 from Rome who had a stillborn fetus at 36 weeks and 1 day of gestation. The placenta demonstrated extensive involvement by regions of hemorrhagic or ischemic necrosis with central and peripheral villous infarctions, and thrombosis of several fetal and maternal vessels with luminal fibrin and platelet depositions.…”
Section: Covid-19 Infection and Stillbirthmentioning
confidence: 99%